Escapement success of silver eels from a German river system is low compared to management‐based estimates. (1st October 2013) - Marohn, Lasse; Prigge, Enno; Hanel, Reinhold
Summary The European eel (Anguilla anguilla) stock experienced a sharp decline during the last decades and is suffering from massive anthropogenic impacts on inland waters. To evaluate the benefit of management measures and to better understand the contribution of single drainage systems to spawner production, knowledge of the respective silver eel escapement is required. Furthermore, a better understanding of environmental conditions that potentially trigger the onset of spawning migration is needed to reduce anthropogenic mortalities during riverine eel migration. Investigations are also necessary to clarify whether fish protecting devices and bypasses at barriers are functional and truly increase eel survival and escapement rates. In this study, total female silver eel escapement from a northern German drainage system (Schwentine River) was assessed over a period of three consecutive years, and downstream migration patterns were compared to potential environmental triggers. Furthermore, the benefit of two fish bypasses (surface and deep) and a trash rack at the hydropower station for the survival of migrating eels was examined, and the spawner quality of escaping silver eels was determined by analysing lipid content and infection intensities with the swimbladder parasite Anguillicoloides crassus. The results indicate that silver eel escapement from the Schwentine drainage system is far below the estimated values underlying the respective eel management plan, highlighting the necessity of direct migration assessments to validate indirect estimations that include multiple assumptions and uncertainties. Major downstream migration events took place during short time periods in autumn and appear to be influenced by river discharge and water temperatures, suggesting that a precise prediction of escapement events is possible. Regarding spawner quality, fat reserves appear sufficient for escaping silver eels to migrate and spawn. However, high A. crassus prevalence and infection intensities are assumed to further reduce the number of potential spawners. Another matter of concern is the high trash rack mortality at the hydropower station that illustrates the need of fish protecting devices that fulfil eel‐specific requirements.